A Modern Strategy to Study the Life Cycle of Lesser House Fly and the Biological Control against the Bacterial Pathogens by Using the Larvae on the Bacterial Cultures - Hussein JabarJasim (Journal of Global Pharma Technology, 2018)
The current research was performed that the lesser house flies were completed the life cycle on the bacteria cultures, also, This study was used the larvae lesser house fliesas a modern biologic control method against several types of pathogenic bacteria include (E. coli, S.aureus and K. pneumonia).The lesser house flies were attracted and laid the eggs on the bacteria cultures during the period that extended from April to May 2016-2018 (two seasons). The Lesser house fly eggs Samples were collected from different regions in south and central of Iraq, Al-Muthanna province and Baghdad province. On the other side, Different bacterial isolates were used such as E. coli, K. pneumonia and S. aureus. The present study was divided into seven groups. The first group was used an organic substance such as a sliced tomato as a control group inside petri dishes. The second and third groups were included E. coli cultured on Maconkey agar and Nutrient agar respectively. While, the fourth and fifth group were included K pneumonia cultured on Maconkey agar and Nutrient agar respectively. The sixth group was included S. aureus cultured on Nutrient agar. Finally, the seventh group was contained only Nutrient agar and Mackonkey agar without bacteria. The second , third , fourth , fifth and sixth , seven group were distributed in the mentioned regions each area was included 10 petri dish from each group which 60 dish in each region. While the eggs were transferred from the other groups to the control group. The seventh group was used to ensure the attraction of the lesser house flies to the bacteria cultures was not because the culture media itself, the dishes of all groups except the control group were opened to allow the flies to attract to bacteria growth and enter the petridishes of groups. Morphological examination of larvae in the present study was carried out, after 7 days of hatching the eggs size of all the groups was approximately 2 millimeters.Keywords: A Modern Strategy, Life Cycle, Biological Control, Larvae Lesser House Fly, Bacterial Cultures.